Analysis of Leadership, Training, Competencies and Organizational Citizenship Behavior on Employee Performance at PT Kalfaz Sadhara - Dhini Anggraini; M. Chaerul Rizky; Emi Wakhyuni (CV. Doki Course and Training, 2026)
Optimal employee performance is not formed automatically, but is influenced by various factors that need to be identified and developed systematically. This study aims to analyze the influence of leadership, training, competence, and organizational citizenship behavior on employee performance at PT Kalfaz Sadhara. This study uses a type of quantitative research with a causal associative approach. The research population is all permanent employees of PT Kalfaz Sadhara totaling 65 people using saturated sampling techniques (census) so that the entire population is used as a research sample. Data collection was carried out through questionnaires with a Likert scale of 1-5, documentation studies, and literature studies. The data analysis technique used is multiple linear regression analysis, where all data processing uses IBM SPSS software. The results of the study show that leadership has a positive and significant effect on employee performance. Training has a positive and significant effect on employee performance. Competence has a positive and significant effect on employee performance. Organizational citizenship behavior has a positive and significant effect on employee performance. Simultaneously, the four independent variables had a significant effect on employee performance and were able to explain the variation in employee performance by 38.7%, while the remaining 61.3% were influenced by other variables outside the research model such as motivation, compensation, work environment, and organizational culture.